IMPLEMENTASI METODE KAISA DALAM MENINGKATKAN HAFALAN AL-QUR’AN SURAT AN-NABA’ DI TK YASMIN JATIKRAMAT - Hilma Kafa Rizkia; Faza karimatul akhlak (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
The process of improving early childhood memorization of the Qur'an depends on the teacher's initial teaching. Teachers can use various approaches or use varied methods to achieve the goal of memorizing the Qur'an. The aim of this research is to find out how the kaisa method is used to memorize Surah An-Naba' from the Al-Qur'an for early age students at Kindergarten Yasmin. The research method used in this research is qualitative research. The results of this research show that the implementation of the kaisa method in improving memorization of the Al-Qur'an Surah An-Naba' in early childhood at Yasmin Kindergarten is quite effective and successful as seen from the achievement of this 2 year target. Students who can complete the An-Naba' letter use the kaisa method within 2 semesters. The supporting factors are the students' basic abilities, high desire and enthusiasm, enthusiastic and competent teachers, and a good family environment. The inhibiting factors are the influence of a bad environment outside of school, lack of support from parents, and limited time at school.